The Role of Financial Ratios on the Financial Distress Prediction - Devi Wahyu Utami; Hanung Eka Atmaja; Heni Hirawati (KINERJA, 2021)
Predictions of financial distress has a central role for the company's going concern aspects. This research aims to empirically prove the role of profitability, leverage and liquidity in financial distress. The research population comprised all companies incorporated in the agricultural sector as well as basic industry and chemical sectors. The research sample obtained as many as 380 observations through the purposive sampling method. This study uses logistic regression analysis. This study provides evidence of significant role between profitability and liquidity on financial distress condition in the agricultural sector as well as the basic industry and chemical sectors. In the basic industry and chemical sectors, leverage has a significant role on financial distress condition.